2012
DOI: 10.4103/0970-1591.94939
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis in laparoscopic renal surgery

Abstract: Hemorrhage is a potential risk at any step of laparoscopic nephrectomies (LNs). The advances in surgical equipment and tissue sealants have increased the safety and efficiency of performing LN and laparoscopic partial nephrectomy (LPN). However, hemostasis remains a major issue and there is still scope for further development to improve haemostatic techniques and devices. In this article a literature review of the current methods and techniques of hemostasis was carried out using the MEDLINE ®/PubMed® resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…Despite the presence of user error, the recall reasons that were consistent with the adverse event outcomes and the corresponding number of units recalled indicated that device based failures also share responsibility. The failure modes identified and the phases in which they occurred were consistent with those outlined in scientific literature (Deng, Meng et al 2002, Champion and Williams 2003, Hamilton, Sims et al 2003, Marshall, Srivastava et al 2003, Brown and Woo 2004, Govekar, Robinson et al 2011, Noble, Smart et al 2011, Hassouna and Manikandan 2012, Lyons and Law 2013, Mansour, El-Nashar et al 2014, Overbey, Townsend et al 2015. Various failures modes were uncommon, yet resulted in severe outcomes when they did occur.…”
Section: Chapter VI Summary and Conclusionsupporting
confidence: 57%
See 4 more Smart Citations
“…Despite the presence of user error, the recall reasons that were consistent with the adverse event outcomes and the corresponding number of units recalled indicated that device based failures also share responsibility. The failure modes identified and the phases in which they occurred were consistent with those outlined in scientific literature (Deng, Meng et al 2002, Champion and Williams 2003, Hamilton, Sims et al 2003, Marshall, Srivastava et al 2003, Brown and Woo 2004, Govekar, Robinson et al 2011, Noble, Smart et al 2011, Hassouna and Manikandan 2012, Lyons and Law 2013, Mansour, El-Nashar et al 2014, Overbey, Townsend et al 2015. Various failures modes were uncommon, yet resulted in severe outcomes when they did occur.…”
Section: Chapter VI Summary and Conclusionsupporting
confidence: 57%
“…Similarly, the two most common mechanisms of endoscopic stapler failure during laparoscopic renal surgery were determined to be inadequate staple lines and failure to release from tissue, which resulted in a high percentage of severe hemorrhage and conversions to open surgery (Hassouna and Manikandan 2012). Outcomes of gastric bypass surgery have shown staple line failures and anastomotic leaks to be a major cause of patient morbidity and death (Champion and Williams 2003, Hamilton, Sims et al 2003, Marshall, Srivastava et al 2003.…”
Section: Endoscopic Stapler Failure Mode Discussionmentioning
confidence: 99%
See 3 more Smart Citations